18F-FDG PET/CT HELPS TO FIND OCCULT CARCINOMA IN A PATIENT WITH MULTIPLE BREAST MASSES AT MAGNETIC RESONANCE IMAGING - Bitencourt, Almir Galvão Vieira; Graziano, Luciana; Tajima, Carla; Makdissi, Fabiana Baroni; Lima, Eduardo Nóbrega Pereira (Mastology, 2019)
52-year-old female patient with diagnosis of invasive carcinoma in the left breast and metastatic lymph node in the right axilla. Magnetic resonance imaging showed multiple breast masses, with four previous negative biopsies in the right breast. 18F-FDG positron emission tomography (PET)/computed tomography (CT) was performed in prone position, dedicated to breast evaluation. It showed increased uptake in a mass in the right breast. After PET/magnetic resonance imaging (MRI) fusion and second-look breast ultrasound, this mass was submitted to percutaneous biopsy, which confirmed a second invasive breast carcinoma and changed patients’ treatment. This is an example of how PET/MRI dedicated devices can improve the evaluation of selected breast lesions.